G634(P) Outcomes & perspectives of a paediatric IBSC course. (May 2019) - Moore, A; Fertleman, C
Abstract : Introduction: At a medical school with a compulsory iBSc, statistical analysis has shown that paediatric iBSc students achieve 2.51% (95% CI 1.22–3.80; p<0.0001) and 1.96% (95% CI 0.31–3.62; p=0.02) higher marks in their final OSCE and SBA examinations respectively. We aimed to explore the potential reasons for this through examining the perspectives of qualified iBSc alumni. Methods: 5 years of paediatric iBSc graduates were contacted for their perspectives on the course. Nvivo was used for framework analysis of their responses. Results: 15/76 alumni responded. Themes identified were: closely supported independence; early clinical exposure; variety within course and research project; ownership and experience of conducting a research project; and developing a foundation in reflective practice. Analysis: Exposure to clinical medicine and research are features common to multiple courses, so independently are unlikely to have conferred an advantage in final exams. More individual to the paediatric iBSc is the combination of students being given much autonomy, whilst being closely supported by a clinical fellow. It is possible that they may take a mentoring role, supporting the students in the development of self-regulated learning strategies, which can be used throughout their university career. Another hallmark of the iBSc is developing a foundation in reflective practice. Although there is conflicting evidence of its association with academic achievement, given the importance of ongoing reflection within professional practice, as emphasised by the GMC, learning this skill is of key benefit regardless. It is possible that the higher final year marks obtained by the iBSC students is not secondary to the course, but to the student cohort themselves. Although the iBSc is oversubscribed and the students are of high calibre, they are not selected based on academic merit, making this less likely. Conclusion: Although we cannot definitively know why paediatric iBSc students have an advantage in their final year exams, examining their opinions of the course gives good insight into the key features which combined make the course unique. In the future, more emphasis and research on the development of self-regulated learning strategies may further improve this and other iBSc courses.